SPECIES COMPOSITION AND DENSITY FLUCTUATION OF LIZARDFISHES EGGS AND LARVAE (SYNODONTIDAE) IN THE TONKIN GULF AREAS OF VIETNAM - Huy, Pham Quoc (Vietnam Journal of Marine Science and Technology, 2017)
Lizardfishes are one of the most common and primary fishes mainly caught by bottom trawls and set gillnets in the Gulf of Tonkin. According to the result of 16 species at early stage sampled from surveys between 2011 and 2013, 4 species and 1 species group were identified: Greater lizardfish (Saurida tumbil), brushtooth lizardfish (S. undosquamis), slender lizardfish (S. elongata), snakefish (Trachinocephalus myops) and lizardfish (Synodus spp. and Saurida sp.). There was an annual fluctuation in the number and encounter frequency of fish larvae and eggs. The density of fish larvae and eggs reduced steadily from 584 to 74 eggs/1,000 m3 seawater and from 30 to 1,785 fish larvae/1,000 m3 seawater. Variation in density was relatively obvious depending on monsoon. Lizardfish’s eggs and larvae were mainly distributed in the north of the Gulf of Tonkin. In Northeast monsoon, while lizardfish’s eggs were primarily concentrated around Bach Long Vi island and scattered around the center of the Gulf of Tonkin, fish larvae were often caught in the offshore areas of Thanh Hoa - Nghe An provinces and the southern sea of Bach Long Vi island. By contrast, in Southwest monsoon, fish larvae and eggs were mainly concentrated in inshore areas such as coastal areas of Quang Ninh and Thanh Hoa provinces and around Cat Ba island.